Kajian Aspek Teknis Pemeliharaan Kerbau Lokal Di Kabupaten Gayo Lues - Sari, Eka Meutia; Abdullah, Mohd. Agus Nashri; Sulaiman, Sulaiman (Jurnal Agripet, 2015)
(Study on The Technical Aspect Management of Local Buffalo in Gayo Lues District)ABSTRACT. The objective of this research to study on the technical aspect management of local buffalo in Gayo Lues district. Forty local buffalo farmers located in three selected sub district of Rikit Gaib, Pantan Cuaca and Dabun Gelang in Gayo Lues were visited and data or informations were collected through interview of the farmers. Data collected included: breed and breeding performance, feed and feeding practices, rearing practices, health aspect and marketing. The data were tabulated and compared with the standard guideline of buffalo management from the Directorate General of Livestock Service (DGLS). Result showed that management practices of local buffalo applied by farmers in Gayo Lues were found very low, only 40.16% of the standard management from DGLS. Application of health (64.57%), and housing (74.78%), while application of breeding and reproduction, rearing practices and feed and feeding were 41.76%, 46.50%, and 17.67% of the standard, respectively.